Comparative Study on the Microstructure and Biodegradation Behavior of Commercialized Pure Mg and Mg-1.0Ca-0.5Sr Alloy in 27 mM HCO3−-SBF: The Influence of the pH Regulation Treatments - Sabri Shafyra; Engku Mohammad Nazim; Nor Hasrul Akhmal Ngadiman; Izman Sudin (Metals, 2023)
The biodegradation behavior of newly developed orthopedic implant materials provides essential insight into the potential degradation products and their ability to match the rate of bone healing prior to complete degradation. Ironically, biodegradation performance is not only influenced by alloy design or advanced surface treatment on the alloy, but also it is dominantly controlled by the specific inorganic species and their concentration in the corrosion media as well as their pH level. In this study, the biodegradation behavior of commercially pure magnesium (CP Mg) and a Mg-1.0Ca-0.5Sr alloy was evaluated in 27 mM <semantics><msubsup>HCO3−</msubsup></semantics>- Simulated Body Fluid (r-SBF) due to its identical ionic species and concentrations with human blood plasma via immersion test, including (i) hydrogen evolution test (H2), (ii) pH trend, and (iii) weight-loss measurement. To simulate the pH regulation by the physiological homeostatic response, the pseudo-physiological solution was treated with two treatments: through a (i) a 24 h corrosion media renewal routine and through the use of (ii) a TRIS-HCL buffer reagent. The Mg-1.0Ca-0.5Sr alloy is shown to have superior corrosion resistance due to grain refinement and unique secondary phases, whereas the daily renewal routine imparts a better emulation of in vivo corrosion control.